World capitalist system and globalization: reconsiderations for achieving sustainable development in Nigeria (2017)
Capitalism with its accompanied liberal ideology has been very successful in expanding its tentacles to and overthrowing other social and economic systems in several parts of the world. The resulting consequence of this historical process is that of globalization which is characterized by increasing homogeneity and interdependence of the various countries of the world on one another. While globalization has been recurrent and become a focus for scholarly discourse, Nigeria right from the time of her independence has remained at a disadvantage position in terms of economic, political, technological and cultural development. Historical events showed that the “supposed giant of Africa” as a peripheral country, has been dancing to the music of the more developed nations, thus experiencing disguised dependency even as an independent republic. However, if the country is serious about achieving its sustainable development goals, it must learn to dictate its own tune and look inwards for the restructuration of its social, economic and political systems in line with her area of strength, as well as addressing her weaknesses. Thus, this paper attempts to describe the current world capitalist system in the light of World-Systems Theory, discuss globalization and then examine key areas Nigeria must look into for the emancipation of its people from the shackles of underdevelopment and dependency. In conclusion, it is recommended that true Federalism and Nationalism should be the watchword and practice of both political leaders and Nigerian citizens in order to achieve grassroots development and national progress.